Relational social work practice with diverse populations : a relational approach - Rosenberger, Judith B. (Essential Clinical Social Work Series, 2014)
Social work and relational theory have long been clinical comrades, given their shared goals and ideals. This close fit continues to be productive as client populations and their needs grow more diverse. Clinical Social Work Practice with Diverse Populations sorts through vital matters of race, ethnicity, sexuality, religion, and social status--and addresses groups and issues often seen in practice but rarely encountered in print--with a profound understanding of the healing power of relational-based treatment. Case examples illustrate all stages of social work process, offering practice guidelines for working with members of diverse groups while emphasizing the uniqueness of every therapeutic dyad. The coverage recognizes the multiple relationships that comprise individuals' lives as well as the individuality that co-exists within group identity. And the contributors carefully show readers how to check themselves for biases and us-versus-them thinking, and how to develop confidence along with clinical skills. Included in this first-of-its-kind text: ·Practice technique and research support for relational therapy. ·Whiteness: Deconstruction of a practice paradox. ·Racial and ethnic diversity, including African American, Latino, Asian American, and Asian Indian clients. ·Religious diversity: evangelical Christians, Muslim, and Orthodox Jewish clients. ·Diversity of sexual identity: LGBT clients. ·Diversity of life-altering experiences: combat veterans, reentry from incarceration, homelessness. ·Plus: background chapters providing a framework for applying relational theory to social work. Bridging the knowledge gaps between the diversity literature and the practical literature, Relational Social Work Practice with Diverse Populations supplies clinical social work professionals, educators, and counselors with tools and concepts for effective, efficient practice.